E-Governance Communication Strategies: Evaluating The Integration Of Digital Media In Citizen-Centric Public Administration In Nigeria - George Nathan Brown; Uwem Asuquo Akpan; Ekang Anietie Etukakpan (International Journal of Economics, Business and Innovation Research, 2025)
This study investigated how digital media contributes to citizen-centred governance through effective communication strategies. It sought to examine the use of digital media for citizen engagement, evaluate its impact on service delivery efficiency, and determine its role in promoting participatory governance. The study was anchored on the Uses and Gratifications Theory and Participatory Communication Theory, which explain active media consumption and citizen involvement in governance processes. A mixed-methods approach combined surveys of 300 respondents with interviews of 15 e-governance officials. Findings revealed that digital media significantly improves citizen engagement through interactive platforms that allow direct feedback and dialogue, enhance service delivery by reducing bureaucratic delays and providing timely information, and encourage participatory governance as citizens actively contribute to policy discussions online. The study concluded that digital media has become a vital tool for advancing citizen-centred governance in Nigeria, as it enhances citizen engagement, improves service delivery efficiency, and fosters participatory governance, though its effectiveness is constrained by infrastructural, institutional, and responsiveness challenges that must be addressed for it to achieve its full potential. The study recommended, among others, that government agencies should strengthen their digital communication strategies to encourage active citizen engagement through responsive and inclusive platforms